Techno economic analysis of using solar water heaters with evacuated tubes in Khartoum, Sudan - Gamil, A.A.A.; Mekhilef, Saad; Said, Suhana Mohd (Sila Science, 2012)
This paper presents the techno-economic study of using solar water heaters employing evacuated tubes in Khartoum, Sudan. Sudan experiences high solar irradiation and is thus a good candidate for harnessing solar energy. One direct application of solar energy is for domestic water heating applications, which has the potential of significant savings on the national energy consumption if used extensively. This study will first introduce the technological and economic benefits of using solar water heated containing evacuated tubes, which have shown better efficiency compared to flat plate solar water heaters. The operational requirements and efficiency of this system will then be compared against the output and efficiency of an electric water heater. The relative costs of each system will also be analyzed and discussed. Also it found that the heat gained from the solar collector was enough for producing hot water and the amount of mass flow rate that was suitable for natural circulation, thus eliminating the need for a driving pump, and reducing the overall cost for the solar water heater system. The techno-economic analysis is then carried out in order to analyze the payback period for a range of number of households required to employ this system. This analysis indicates that a saving was 415.2 USD per year for 8 households and the payback period ranged between 0.98 and 1.43 year, thus rendering this technology as an attractive option for energy and cost savings for domestic applications. Â© Sila Science.